Personalized and Biomarker-Guided Non-Invasive Brain Stimulation in Stroke Rehabilitation: A Systematic Review - Jauharotul Jannah; Firman Akbar Islami (Green Publisher Indonesia, 2026)
Stroke causes significant disability, yet conventional rehabilitation demonstrates limited efficacy, particularly in severe cases. Non-invasive brain stimulation (NIBS) such as repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS) offers a promising alternative; however, outcomes vary considerably due to the prevailing